A Coupling Agent's Inclusion Affects Functional Groups and Heat Resistance in Energy Storage Materials - Fauziyah, Nur Aini; Perwitasari, Dyah Suci; Wardhani, Primasari Cahya; Ernawati, Dira; Nabilla, Nabilla (Chemistry Department, The University of Brawijaya, 2023)
The study of functional groups and heat resistance of energy-importing materials, as well as the inclusion of coupling agents, were the primary subjects of this article. 3-(trimethoxysilyl) propyl methacrylate was the coupling agent employed in this study to alter the surface of the silica in the composite material being created. Furthermore, the emergence of bifunctional organometallic (silane) connecting groups allowed the coupling agent to improve the energy storage material's heat resistance. Through the using of dynamic mechanical analysis, scanning electronic microscopy, and thermal tests. It was determined how the type of coupling material affected the interfacial bond strength. According to the findings, there was a significant interaction between the coupling material and the filler surface that had an impact on the material's heat resistance.